An update on preoperative assessment and preparation of surgical patients with obstructive sleep apnea. Issue 1 (February 2018) - Madhusudan, Poorna; Wong, Jean; Prasad, Arun; Sadeghian, Elena; Chung, Frances F.
Abstract : Purpose of review: There is a high prevalence of obstructive sleep apnea (OSA) in the surgical population, however, a significant proportion of patients are undiagnosed. The Society of Anesthesia and Sleep Medicine (SASM) has issued recent guidelines for preoperative assessment and preparation of patients with known or suspected OSA. The purpose of this review is to highlight key points in the new guidelines and explore the possibilities of different strategies in optimizing patients with OSA preoperatively. Recent findings: Recent knowledge on phenotypes and endotypes has provided a better understanding of the disease and its underlying pathogenesis. Phenotypes refer to the predominant morphological characteristics of an individual whereas endotypes refer to the predominant underlying mechanism of the disease. Phenotypes and endotypes in OSA are heterogenous. Heterogeneity in the pathogenic mechanisms implies that opportunities other than the use of continuous positive airway pressure (CPAP) may exist to optimize or manage OSA patients preoperatively. Summary: The prevalence of OSA in surgical patients is high. SASM has made recommendations in their published guidelines for the optimum preoperative preparation of patients with OSA. In the future, research may shift towards finding the underlying mechanism of OSA for targeted therapy. Abstract : Supplemental Digital Content is available in the text